The quality of banking services and their role in achieving customer satisfaction in private banks Exploratory study on the customers of banks in the city of Baghdad, 2019 - خضير أحمد, أحمد (Finance and Business Economies Review, 2019)
The study aimed to determine the role of the concept of quality of banking services in the satisfaction of customers in Iraqi private banks. The study was based on the analytical descriptive method. The questionnaire was used as a data collection tool. The study population is represented by all clients in private banks in Baghdad. It has been selected a random Of (120) customers distributed the questionnaire of the study and retrieved (103) valid questionnaire for analysis, and after the appropriate statistical analysis of the data, the study found: the existence of a positive correlation relationship between the quality of banking services dimensions (quality of tangible assets, The availability of banking services, reliability, interaction, empathy, confidentiality and privacy) and customer satisfaction in private banks in Baghdad.as well as The level of availability of quality banking services was great. The most tangible aspects were followed by confidentiality and privacy followed by easy access to service, followed by sympathy and came at last rank after reliability. It also found that the level of customer satisfaction in private banks was significant. The study recommended more attention to the dimensions of the quality of banking services in private banks in the city of Baghdad by the senior management on how to achieve the means which can be achieved by them. And preparing and implementing specialized training programs in modern administrative systems for bank employees and work on refining their skills with full knowledge of their work tasks so that they can perform